Optimasi Proses Cooking Tandan Kosong Kelapa Sawit dengan Metode Soda Metilantrakuinon (MAQ) dan Digester Liquor Tersirkulasi untuk Produksi Dissolving Pulp - Fadila, Rawdatul; Evelyn; Zahrina, Ida (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
Dissolving pulp is a raw material in the textile, plastic, and other cellulose-derived products industries, which has a high content of α-cellulose (≥90%), high degree of brightness, low hemicellulose and lignin content. Demand for dissolving pulp continues to increase, so a sustainable alternative raw material source is required. Empty bunches from oil palm industry waste can potentially be processed into dissolving pulp. This study aims to determine the effect of cooking temperature, cooking time and NaOH concentration on yield, kappa number and viscosity and to obtain the optimum conditions for cooking oil palm empty bunches for dissolving pulp using 2-methylantraquinone (MAQ) soda with a circulating liquor digester. Prehydrolysis of the raw materials was conducted at 150 °C for 180 min, followed by soda cooking with 0.1% MAQ at 140–160 °C for 120–240 min using NaOH concentrations of 10–20%. Optimization was conducted using Design Expert software with Response Surface Methodology (RSM) model Central Composite Design (CCD). Pulp from the cooking process produced yields with a range of 23.4-51.56%, kappa numbers of 6.97-19.44 and viscosity of 6.21-9.13 cP. Optimal conditions were obtained from RSM at 160°C, 120 minutes cooking time, and 20% NaOH concentration, with an estimated yield of 46.9%, kappa number of 10.22, and viscosity of 7.06 cP. This study confirms that the production of dissolving pulp from oil palm empty fruit bunches for dissolving pulp with MAQ soda process and circulating digester liquor was successfully carried out.